Comparison of injury severity scores (ISS) obtained by manual coding versus “Two-step conversion” from ICD-9-CM - Abajas-Bustillo, Rebeca; Amo-Setién, Francisco José; Leal-Costa, César; Ortego-Mate, María del Carmen; Seguí-Gómez, María; Durá-Ros, María Jesús; Zonfrillo, Mark R. (PloS one, 2019)
The International Classification of Diseases (ICD) is the standard diagnostic tool for classifying and coding diseases and injuries. The Abbreviated Injury Scale (AIS) is the most widely used injury severity scoring system. Although manual coding is considered the gold standard, it is sometimes unavailable or impractical. There have been many prior attempts to develop programs for the automated conversion of ICD rubrics into AIS codes. To convert ICD, Ninth Revision, Clinical Modification (ICD-9-CM) codes into AIS 2005 (update 2008) codes via a derived map using a two-step process and, subsequently, to compare Injury Severity Score (ISS) resulting from said conversion with manually coded ISS values. A cross-sectional retrospective study was designed in which medical records at the Hospital Universitario Marqués de Valdecilla of Cantabria (HUMV) and the Complejo Hospitalario of Navarra (CHN), both in Spain, were reviewed. Coding of injuries using AIS 2005 (update 2008) version was done manually by a certified AIS specialist and ISS values were calculated. ICD-9-CM codes were automatically converted into ISS values by another certified AIS specialist in a two-step process. ISS scores obtained from manual coding were compared to those obtained through this conversion process. The comparison of obtained through conversion versus manual ISS resulted in 396 concordant pairs (70.2%); the analysis of values according to ISS categories (ISS<9, ISS 9-15, ISS 16-24, ISS>24) showed 493 concordant pairs (87.4%). Regarding the criterion of "major trauma" patient (i.e., ISS> 15), 538 matching pairs (95.2%) were obtained. The conversion process resulted in underestimation of ISS in 112 cases (19.9%) and conversion was not possible in 136 cases (19%) for different reasons. The process used in this study has proven to be a useful tool for selecting patients who meet the ISS>15 criterion for "major trauma". Further research is needed to improve the conversion process.